The Administrative Performance of the Laguna Lake Development Authority on the Small Lakes of the Laguna de Bay Region, Philippines - Brillo, Bing Baltazar C. (Animo Repository, 2019)
Few studies have dealt with small lakes in the Philippines, particularly aspects of their governance, which translate to information deficit on the status of administration of many lakes in the country. At the core of governance in any lake is its administrative agency, and in the eight crater lakes of San Pablo City, it is the Laguna Lake Development Authority (LLDA). Under this context, this article examines the administrative performance of the LLDA on the eight small lakes (i.e., Sampaloc Lake, Bunot Lake, Palakpakin Lake, Calibato Lake, Mohicap Lake, Pandin Lake, Yambo Lake, and Tadlac Lake) of the Laguna de Bay Region. The study evaluates the agency using four criteria deemed fundamental in managing, conserving, and developing small lakes: (1) having an approved management and development plan (MDP); (2) regulating fish pens and cages; (3) implementing the shoreline easement; and (4) conducting maintenance activities. Using data from interviews, site observations, documents, reports, and other secondary sources, the study contends that the LLDA’s performance is ambivalent because its management of the small lakes can be characterized as slow and lacking in follow-through in the MDP issue; unsatisfactory in the regulation of aquastructure and shoreline easement; but decent in water quality monitoring, clean-up operations, and fingerlings dispersal. On the whole, the assessment exemplifies the inconsistent actions of the LLDA and underscores the long-term commitment and accountability of the agency in governing the crater lakes.